Bifunctional iminophosphorane catalyzed amide enolization for enantioselective cyclohexadienone desymmetrization. - Poh, CYX; Rozsar, D; Yang, J; Christensen, KE; Dixon, DJ (Wiley, 2023)
The organocatalytic enolization of 2-arylacetamides, followed by an enantioselective intramolecular conjugate addition to tethered 2,5-cyclohexadienones, yielding 3D fused N-heterocycles, is described. The transformation represents the first strong activating group-free activation of carboxamides via α-C-H deprotonation in a metal-free, catalytic, and enantioselective reaction, and is achieved by employing a bifunctional iminophosphorane (BIMP) superbase.